Computational parasites and hydropower: A political ecology of Bitcoin mining on the Columbia River. (March 2022) - Lally, Nick; Kay, Kelly; Thatcher, Jim
Over the past three years, the dams of Chelan County, Washington, its watershed and fish, the electrical grid and the laborers who maintain it, and cleared land with warehouses filled with computers, have all been enrolled as part of the decentralized digital infrastructure of Bitcoin. While popular accounts of the Bitcoin network correctly report the massive scale of energy it consumes and its potential environmental ramifications, in practice, the material geographies of Bitcoin are highly uneven and intertwined with specific infrastructural, ecological, and economic systems. In this article, we examine Bitcoin's impacts on Chelan County, untangling the processes that occur as the distributed, digital infrastructure consumes the very real material resources of one place to produce digital goods used in another. In so doing, we examine not only the material costs of networks like Bitcoin, but also their historical ties to older processes of accumulation.